Air pollution and worker productivity - Matthew Neidell; Nico Pestel (IZA World of Labor, 2023)
Environmental regulations are typically considered to be a drag on the economy. However, improved environmental quality may actually enhance productivity by creating a healthier workforce. Evidence suggests that improvements in air quality lead to improvements in worker productivity at the micro level across a range of sectors, including agriculture, manufacturing, and the service sectors, as well as at more aggregate macro levels. These effects also arise at levels of air quality that are below pollution thresholds in countries with the highest levels of environmental regulation. The findings suggest a new approach for understanding the consequences of environmental regulations.
Keywords: I31; J24; Q53; 330; air pollution; worker productivity; environmental policy